The Effect of Multiple Role Conflict and Social Support on Organizational Commitment in Career Women in Medan - T. Elfira Rahmayati; Khairunnida Khairunnida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the effect of multiple role conflict and social support on organizational commitment. The population of this study is a married career woman in Medan. By using purposive sampling method with a sample of 300 people. Data were collected using a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple regressions. The results of this study indicate that there is a negative effect of multiple role conflict on organizational commitment with the regression coefficient having a value of -0.210, there is effect of social support on organizational commitment with a value of 0.000 < 0.005 and the regression coefficient has a value of 0.396 and there is an effect of multiple role conflict and support social simultaneously with the regression coefficient value has a value of 0.280 or 28%.